2020
DOI: 10.3846/tede.2020.11908
|View full text |Cite
|
Sign up to set email alerts
|

Economy-Water Nexus in Agricultural Sector: Decomposing Dynamics in Water Footprint by the Lmdi

Abstract: Traditional economic activities induce environmental pressures. In order to ensure sustainable economic growth, one needs to decouple it from the environmental pressures. Sustainable growth of the agricultural sector is topical in the sense that economic activity supports rural populations, whereas the resulting environmental pressures may affect diverse groups of population. Thus, the analysis of water footprint related to crop farming is important in the sense of efficient resource use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In addition, when the indirect influence of the driving factor through other factors was larger, the influence of the two methods was reversed in some regions. Previous studies have shown that the main positive driving factors of the agricultural GWF were economic development status and population Cui et al, 2020), planting structure and scale (Su et al, 2020). The main negative driving factors were investment change in crop planting, urbanization , and industrial structure adjustment (Cui et al, 2020).…”
Section: Frontiers In Environmental Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when the indirect influence of the driving factor through other factors was larger, the influence of the two methods was reversed in some regions. Previous studies have shown that the main positive driving factors of the agricultural GWF were economic development status and population Cui et al, 2020), planting structure and scale (Su et al, 2020). The main negative driving factors were investment change in crop planting, urbanization , and industrial structure adjustment (Cui et al, 2020).…”
Section: Frontiers In Environmental Sciencementioning
confidence: 99%
“…Based on the distribution of the study areas, China is the key area of these studies. The main research methods are structural decomposition analysis (SDA) (Wan et al, 2016;Liao et al, 2021), logarithmic-mean divisia index (LMDI) exponential decomposition (Li et al, 2017;Zhang et al, 2019;Cao et al, 2020;Cui et al, 2020;Su et al, 2020;Feng et al, 2021;Fu et al, 2021;Chen et al, 2022) and stochastic impacts by regression on population, affluence, and technology (STIRPAT) (Jin et al, 2016;Fan and Fang 2020;Zhang et al, 2020) (see Table 1). The SDA method is based on an input-output model and requires input-output coefficients and final demand for each sector (Su and Ang 2012;Jin et al, 2016); however, the LMDI method has no residual term (Ang 2005).…”
Section: Open Accessmentioning
confidence: 99%
“…[17][18][19] LMDI model is a factorization method without residual errors, which is widely applied in environment and resource areas, including land, carbon emission, energy, and water resources. [20][21][22][23][24] Therefore, the LMDI model is chosen in this research.…”
Section: Introductionmentioning
confidence: 99%
“…The LMDI model is a factor decomposition method that does not generate residual error [22]. The application of LMDI is essentially for resources and the environment, such as carbon emissions, energy, land, and water resources [23][24][25][26][27][28]. At present, LMDI research on water resources has calculated the driving factors at national level or the city level [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%